The Effect of Quadriceps Strengthening Exercise and Ultrasound on Improving Functional Activity in Patients with Knee Osteoarthritis - isidorus jehaman; Debi Saputra (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Knee osteoarthritis (OA) is a degenerative joint disease with increasing prevalence due to population aging. WHO data (2022) shows OA affects 528 million people globally. In Indonesia, OA prevalence in the population >45 years reaches 24.7%, with knee OA contributing 65% of cases, highest in West Java, specifically Bandung City (26.3%). The pathophysiology of knee OA involves cartilage degradation, synovial inflammation, and quadriceps muscle weakness. This study aims to determine the effect of combining ultrasound therapy and quadriceps strengthening exercises on improving functional activity in knee OA patients at RSAU Dr. M. Salamun Bandung in 2025. Methods: The study used a quasi-experimental design with a one-group pre-test and post-test approach on 12 patients selected via purposive sampling. The intervention, combining ultrasound therapy and quadriceps strengthening exercises, was administered twice weekly for 3 weeks. Functional activity was measured using the WOMAC Index before and after the intervention. Data analysis employed the Dependent T-test after the Shapiro-Wilk normality test confirmed a normal distribution (Sig. ≥ 0.05). Results: The Dependent T-test showed a significant improvement in functional activity post-intervention. The mean WOMAC score post-test was better than pre-test. Statistical analysis revealed a Sig. (2-tailed) value of 0.000 (≤ 0.05), indicating a significant difference between functional activity before and after the intervention.Conclusion: There is a significant effect of combining ultrasound therapy and quadriceps strengthening exercises on improving the functional activity of knee osteoarthritis patients at RSAU Dr. M. Salamun Bandung in 2025.